Kemampuan Chaetoceros calcitrans (Paulsen) Takano dalam Menurunkan Kadar Logam Berat Tembaga (Cu) pada Limbah Tekstil - Fitriyanto, Eko Bambang; Soeprobowati, Tri Retnaningsih; Hariyati, Riche (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Textile industries produce waste as one of the industrial product processing. One of pollutants in liquid waste is heavy metal ion. The heavy metals which were found in textile waste is Copper. Copper is one of the metals which are needed in trace element and essentially for the organism. But if its amounts were high, the function will change as a toxin in the body. Physical and chemical remediation method need expensive price but it is not effective. Another alternative method that can be used is bioremediation with micro algae, called phycoremediation. One of micro algae that was used for phycoremediation agent is Chaetoceros calcitrans (Paulsen) Takano is easy to be cultured. The objective of this research is to study the growth of the population and the percentageof Cu reduction after inoculation using C. calcitrans (Paulsen) Takano.Chaetoceros calcitrans (Paulsen) Takano was cultivated in textile waste in seven days wereobserved the population and the percentage of Cu reduction. The environment factors such as salinity, pH, light intensity should be kept for their stability. During seven days,C. calcitrans (Paulsen) Takano able decreased 20% of Cu concentration ( from 0.595 mg/l to 0.478 mg/l ) in seven days and the number of cells 2,8 Ã— 106 cell/ml.Â Keywords: Chaetoceros calcitrans, heavy metal, phycoremediation, copper